Admiral Bill Halsey : a naval life - Hughes, Thomas Alexander, 1963- (Harvard University Press, 2016)
"William Halsey was the most famous naval officer of World War II. His fearlessness in carrier raids against Japan, his steely resolve at Guadalcanal, and his impulsive blunder at the Battle of Leyte Gulf made him the "Patton of the Pacific" and solidified his reputation as a decisive, aggressive fighter prone to impetuous errors of judgment in the heat of battle. In this definitive biography, Thomas Alexander Hughes punctures the popular caricature of the "fighting admiral" to reveal the truth of Halsey's personal and professional life as it was lived in times of war and peace. Halsey, the son of a Navy officer whose alcoholism scuttled a promising career, committed himself wholeheartedly to naval life at an early age. An audacious and inspiring commander to his men, he met the operational challenges of the battle at sea against Japan with dramatically effective carrier strikes early in the war. Yet his greatest contribution to the Allied victory was as commander of the combined sea, air, and land forces in the South Pacific during the long slog up the Solomon Islands chain, one of the war's most daunting battlegrounds. Halsey turned a bruising slugfest with the Japanese navy into a rout. Skillfully mediating the army and navy's constant strategy disputes--as well as the clashes of ego between General Douglas MacArthur and Admiral Chester Nimitz--Halsey was the linchpin of America's Pacific war effort when its outcome was far from certain."--Provided by publisher.